Rent-a-(really shy!)-girlfriend. 3 - Miyajima, Reiji (Kodansha USA Publishing, 2022)
"The official spinoff manga of Rent-A-Girlfriend, the rom-com turned hit anime, features fan-favorite Sumi, the shy girl longing to come out of her shell. Written and illustrated by original creator Reiji Miyajima! Catch up on the manga before Rent-A-Girlfriend returns for a second anime season, coming soon! AN UNEXPECTED CLIENT. Spurred by Mizuhara and determined to make her dream come true, Sumi takes on another date...only to discover that her client is a child! And it's not only her work life that's getting hectic. Trips to the nail salon, movie theater, and ramen shop might seem ordinary to most people, but for a girl with poor communication skills, they're veritable adventures!"--Publisher.